2022
DOI: 10.1007/s00384-022-04110-0
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin injection for the treatment of chronic anal fissure: uni- and multivariate analysis of the factors that promote healing

Abstract: Purpose Anal fissure is caused by a pathological contraction of the internal anal sphincter. Lateral internal sphincterotomy remains the gold standard for the treatment of fissure. Botulinum toxin injections have been proposed to treat this condition without any risk of permanent injury of the internal sphincter. We investigate clinical and pathological variables and the effects of different dosage regimens of botulinum toxin to induce healing in patients with idiopathic anal fissure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
6
0
1
Order By: Relevance
“…Brisinda et al in a recent retrospective study on 1.003 patients reported that toxin dose signi cantly correlates with healing rate: the higher the dose used, at least up to 50 IU, the more conspicuous the number of patients healed. The authors stated the best results were obtained when, in patients with posteriorly located ssure, the toxin was injected into the internal sphincter at the anterior commissure [29]. In the presented study all patients underwent injection of a total of 80 U of Botox A posteriorly, close to the ssure into two sites: 40 U at 5 o'clock and 40 U at 7 o'clock.…”
Section: Discussionmentioning
confidence: 82%
“…Brisinda et al in a recent retrospective study on 1.003 patients reported that toxin dose signi cantly correlates with healing rate: the higher the dose used, at least up to 50 IU, the more conspicuous the number of patients healed. The authors stated the best results were obtained when, in patients with posteriorly located ssure, the toxin was injected into the internal sphincter at the anterior commissure [29]. In the presented study all patients underwent injection of a total of 80 U of Botox A posteriorly, close to the ssure into two sites: 40 U at 5 o'clock and 40 U at 7 o'clock.…”
Section: Discussionmentioning
confidence: 82%
“…Choosing an injection site different from the site of the fissure was based on the concept that fibrosis of the internal sphincter is more prominent in the zone of the anal fissure than in other sites in the smooth muscle 20 . The fibrosis may reduce compliance of the internal sphincter and block the action of the toxin 14 , 19 , 21 , 22 . In patients with posterior chronic anal fissures, anterior injection was more effective in inducing healing than posterior injection 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to surgical referrals as a general or colorectal surgeon may be more likely to recommend LIS to a patient at low risk of incontinence as this is the “gold standard,” 1 although guidelines suggest chemodenervation prior to LIS to avoid permanent damage to the internal anal sphincter. 2 Additionally, Botox has had variable results in different studies, with 1 recent retrospective single-center study 13 of over a thousand patients noting a dose-dependent high healing rate (93.9%) with no recurrences in 71 months and no incontinence. In contrast, a recent randomized control trial 4 comparing botulinum injection with topical diltiazem to botulinum injection alone noted only a 52% healing rate in the experimental group with a 30% transient incontinence rate and an 83.3% recurrence rate in 10 years.…”
Section: Discussionmentioning
confidence: 99%